PENTINGNYA PENERAPAN PERATURAN PEMERINTAH NOMOR 44 TAHUN 2022 KEPADA PENGUSAHA KENA PAJAK DI WILAYAH JABODETABEK - IGP, Ratih Andaningsih; Novita, Novita; Muis, Muhammad Abdul (Jurnal Riset Akuntansi Politala, 2023)
The purpose of this study is to find out more about PP No 44 of 2022 regarding the application of value added tax on goods and services and sales tax on luxury goods to taxpayers and taxable entrepreneurs in the Jabodetabek Region. The researchÂ method used is a qualitative descriptive method with a factor analysis content approach using 25 respondent data. Researchers used direct interviews with medium sized business people and franchise business people in the Jabodetabek area.This research is very useful to find out the level of understanding of medium sized trading businesses regarding the implementation of Government egulation No 44 of 2022 concerning the application of the value added tax on goods and services and the sales tax on luxury goods and its implementation in sales transactions.The limitations of this research are only limited to the application of value added tax on goods and services and sales tax on luxury goods in the Greater Jakarta area and its surroundings. The reults of the research are to increase public understanding, especially traders and medium-sized businesses for the implementation of PP No 44 of 2022 concerning the application of value added tax on goods and sales tax on luxury goods that support the national income sector